Isomonodromy for the Degenerate Fifth Painlev e Equation (2017)
This is a sequel to papers by the last two authors making the Riemann{Hilbert correspondence and isomonodromy explicit. For the degenerate fifth Painlev e equation, the moduli spaces for connections and for monodromy are explicitly computed. It is proven that the extended Riemann{Hilbert morphism is an isomorphism. As a consequence these equations have the Painlev e property and the Okamoto{Painlev e space is identified with a moduli space of connections. Using MAPLE computations, one obtains formulas for the degenerate fifth Painlev e equation, for the B acklund transformations.